Carbohydrate-based approach for the total synthesis of 1,3-polyol/alpha-pyrone antifungal natural products - Ramana, Chepuri V.; Srinivas, B.; Puranik, Vedavati G.; Gurjar, M. K. (Journal of Organic Chemistry, 2005)
An elimination and stereoselective hydrogenation of alpha-D-glucoheptonic-gamma-lactone derivative has been applied to prepare a differentially protected anti,anti-1,3,5-triol system, the utility of which has been extended for the total synthesis of anti-fungal 1,3-polyol/alpha-pyrone natural products.

India: apremier destination for outsourcing - Chorghade, Mukund S.; Chorghade, V. M.; Gurjar, Mukund K.; Ramana, Chepuri V.; Kamerkar, A. V.; Zafran, H.; Mashelkar, Raghunath Anant (Speciality Chemicals Magazine, 2005)

Expeditious assembly of 3,4-benzannulated 8-oxabicyclo[3.2.1]octane systems by [2+2+2] alkyne cyclotrimerisation: Total synthesis of (-)-bruguierol A - Ramana, Chepuri V.; Salian, Sumanth R.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2007)
Facile construction of benzene-fused 8-oxabicyclo[3.2.1]octane systems by employing a cross alkyne cyclotrimerisation reaction was explored. With this procedure, (-)-bruguierol A was synthesised, and its absolute configuration was established.
Keywords: cyclotrimerisation; epoxidation; Total synthesis; Wilkinson's catalyst

Steric control in pd-mediated cycloisomerization of sugar alkynols: documentation of a rare allylic epimerization - Ramana, Chepuri V.; Patel, Pitarnbar; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Pd-mediated cycloisomerization of C3-alkynylated glucofuranosyl derivatives revealed a dominance of steric factors over electronic factors. However, the intermediate glycals were epimerized prior to the ketalization and afforded the more stable cis-fused bicyclic ketals. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Bis-Homopropargylic Alcohols; Oriented Organic-Synthesis; Nucleophilic-Attack; Room-Temperature; Palladium; Chemistry; Heterocycles; Complexes; Transformations; Sonogashira

Total syntheses of schulzeines B and C - Gurjar, Mukund K.; Pramanik, Chinmoy; Bhattasali, Debabrata; Ramana, Chepuri V.; Mohapatra, Debendra K. (Journal of Organic Chemistry, 2007)
Schulzeines B (2) and C (3) were synthesized by a convergent strategy using epimeric tricyclic lactam building blocks, 4 and 5, and the C28 fatty acid side chain 6. Syntheses of tricyclic lactams (4/5) were achieved by Bischler-Napieralski reaction. Sharpless asymmetric dihy-droxylation and BINAL-H-mediated asymmetric reduction of an enone was employed to prepare the key fatty acid side chain 6. The spectral as well as analytical data of 2 and 3 were in good agreement with the reported data for the natural products, thus confirming their assigned structures.
Keywords: Alpha-Glucosidase Inhibitors; Asymmetric Dihydroxylation; Adjuvant Activity; Pinellic Acid; Ketones; Reduction; Reagents; Configuration; Imbricatine; Alkaloids

Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium

Effect of the allylic substituents on ring closing metathesis: the total synthesis of stagonolide B and 4-epi-stagonolide B - Giri, Awadut G.; Mondal, Mohabul A.; Puranik, Vedavati G.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2010)
The total syntheses of stagonolide B and its 4-epimer were carried out to probe into how the relative stereochemistry of allylic hydroxy groups and their protecting groups influence the efficiency of the ring closing metathesis.

Investigation of magnetic anisotropy in Co nanoparticles using ferromagnetic resonance technique - Sendilkumar, A.; Kasture, Manasi; Patel, Pitamber; Ramana, Chepuri V.; Bhagavatula L. V. Prasad; Srinath, S. (Journal of Physics: Conference Series, 2010)
Using ferromagnetic resonance (FMR) technique, we have investigated the temperature dependence and angular dependence of line width and resonance magnetic field of Co nanoparticles capped with novel alkane carboxylic acids of varying chain lengths. The magnetic properties such as blocking temperature and anisotropy sensitively depend on the chain length as evidenced by the temperature dependence of line width. These results indicate that the magnetic properties of these samples are critically governed by the interparticle interactions which are decided by the chain length. The presence of anisotropy even up to very high temperature above the blocking temperature observed in these studies confirms the presence of inter-particle magnetic interactions as well as intra-particle exchange interaction between the core and shell regions as evidenced by our earlier ac susceptibility and transverse susceptibility measurements on similar system.

Divergent Pd(II) and Au(III) mediated nitroalkynol cycloisomerizations - Patel, Pitambar; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2011)
A new cycloisomerization reaction comprising the simultaneous addition of nitro and alcohol groups across C C leading to skeletally diverse small molecules is documented.

[Pd]-mediated omega-alkynone cycloisomerization approach for the central tetrahydropyran unit and the synthesis of C(31)-C(48) fragment of aflastatin A - Narute, Sachin B.; Kiran, Neella Chandra; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2011)
A concise assembly of the central tetrahydropyran unit of aflastatin A featuring a Pd-mediated alkynone cycloisomerization to provide a glycal and its subsequent stereoselective hydroboration to deliver the requisite stereochemistry at C(33) and C(34) centers is documented.

Synthesis and structural characterization of homochiral homo-oligomers of parent CIS- and trans-furanoid-beta-amino acids - Pandey, Sunil K.; Jogdand, Ganesh F.; Oliveira, Joao C. A.; Mata, Ricardo A.; Rajamohanan, Pattuparambil R.; Ramana, Chepuri V. (Chemistry-A European Journal, 2011)
The synthesis of homochiral homo-oligomers of cis- and trans-3-aminotetrahydrofuran-2-carboxylic acids (parent cis- and trans-furanoid-beta-amino acids, referred to as ``cis-/trans-FAA'') has been carried out to understand their secondary structures and their dependence on the ring heteroatom. The oligomers of two diastereomers have been shown to have a distinct left-handed helicity. The cis-FAA homo-oligomers show a 14-helix structure, in contrast to the homo-oligomers of cis-ACPC, which adopt a sheet like structure. The trans-FAA homo-oligomers were found to adopt a 12-helix structure, the same trend found in trans-ACPC homo-oligomers. With the help of ab initio calculations, the structural features of cis-ACPC and cis-FAA hexamers were compared. We believe that the more compact packing of the cis-FAA hexapeptide should be due to a more favorable interaction between the ring and the backbone amide hydrogen.
Keywords: ab initio calculations; Amino acids; Density functional calculations; Peptides; secondary structures

InCl3-mediated addition of indole to isatogens: an expeditious synthesis of 13-deoxy-isatisine A - Kumar, Chepuri V. Suneel; Puranik, Vedavati G.; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
A strategy directed towards the total synthesis of isatisine A that involves several late-stage metal-catalyzed transformations that address the key carboncarbon and carbonheteroatom bond formations has been developed. As a part of this strategy, methods for the addition of indoles to isatogens that lead selectively to either 2,2-disubstituted N-hydroxyindolin-3-one or 2,2-disubstituted indolin-3-one compounds have been developed by employing InCl3 as a catalyst or as the reagent. The present methods provide the first examples of the additions of indoles to the isatogen nucleus. To demonstrate its viability, the synthesis of 13-deoxy-isatisine A has been completed in ten steps from a known and easily available lactone.
Keywords: indium; indoles; isatogens; Natural products; Total synthesis

Ruthenium-catalyzed C6-propenylation reactions of substituted pyridine derivatives: directed and direct C-H activation - Goriya, Yogesh; Ramana, Chepuri V. (Chemistry-A European Journal, 2012)
Keywords: alkenylation; C?H activation; nitrogen heterocycles; pyridine derivatives; ruthenium

Synthesis and structural characterization of homochiral homo-oligomers of cis-gamma-methoxy-substituted cis- and trans-furanoid-beta-amino acids - Giri, Awadut G.; Jogdand, Ganesh F.; Rajamohanan, Pattuparampil R.; Pandey, Sunil K.; Ramana, Chepuri V. (European Journal of Organic Chemistry, 2012)
Herein we describe the synthesis of cis-/trans-3-aminotetrahydrofuran-2-carboxylic acids (cis-/trans-FAA) having a ?-methoxy group cis to the amine. The homo-oligomers of these two diastereomeric FAAs have been prepared. Preliminary investigation of their solution secondary structures revealed that they are the same as the homo-oligomers of the parent cis-/trans-FAA with the methoxy group only being a spectator substituent.
Keywords: Amino acids; helical structures; Oxygen heterocycles; Peptides

Total synthesis and structural revision of stagonolide D - Vadhadiya, Paresh M.; Puranik, Vedavati G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The total synthesis of the putative structure of stagonolide D has been completed. The relative and absolute configuration of stagonolide D was established by synthesizing its optical antipode. The adopted strategy involves the construction of the central macrolide employing ring-closing metathesis (RCM), followed by selective protecting group manipulations and a final concomitant −OTBS deprotection and displacement of an −OMs placed next to it, resulting in the formation of the epoxide ring.

Total synthesis of (–)-sacidumlignans B and D - Rout, Jeetendra Kumar; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The first total synthesis of naturally occurring sacidumlignans A (1), B (2), and D (4) was executed and the absolute configuration of 2 and 4 was determined. A diastereoselective α- methylation of a lactone was used as the key step for the control of the chiral centers of the central lignan core. An acid mediated dehydrative cyclization of an aldehyde to construct the dihydronaphthalene unit of 2 and the aromatization of the intermediate dihydronaphthalene derivative to synthesize 1 are the key reactions employed in this regard.

Evaluation of viability of halogen•••O2N interactions: insight form crystal packing in a series of isomeric halo and nitro substituted triaryl compounds with modular positioning of halogen and NO2 groups - Ramana, Chepuri V.; Goriya, Yogesh; Durugkar, Kulbhushan A.; Chatterjee, Soumitra; Krishnaswamy, Shobhana; Gonnade, Rajesh G. (CrystEngComm, 2013)
A series of isomeric triaryl compounds with a modular positioning of the halogen and NO2 groups have been synthesized by the azide–alkyne “click reaction” and have been characterized by single crystal X-ray structure analysis. This isomeric series has provided an opportunity for understanding the efficiency of the bifurcated halogen⋯NO2 synthon in the organization of the molecules in the crystalline lattice. The changes in molecular conformation, crystal packing and supramolecular aggregation due to the change in the relative positioning of the complementary groups, halogen atom and the NO2 group on ring A and ring C respectively, have been discussed. All the isomers synthesized are crystalline and establish the triazole as a reliable linker for crystal engineering oriented molecular synthesis. The 2-NO2 derivatives display in general, a helical architecture and 3-NO2 derivatives exhibit a centrosymmetric dimeric assembly via the complementary C–H⋯O interactions leading to either a helical or a 2-dimensional sheet pattern. The molecular organization in 4-NO2 derivatives revealed in general a 2D sheet pattern.

Modular total synthesis of (+/-)-trigonoliimine C - Reddy, B. Narendraprasad; Ramana, Chepuri V. (Chemical Communications, 2013)
A convergent total synthesis of trigonoliimine C has been executed by employing three catalytic transformations in sequence. The key reactions that have been developed in this context include the [Au]-catalyzed addition of protected tryptamine to isatogens and the reduction of N-OH to NH with hydrazine monohydrate.

One-pot process for the conversion of aroyl chlorides to acyl thioureas - Ramana, Chepuri V.; Senthilkumar, B. (WO2014087431A1, WO2014087431A8, 2013)
The present invention disclose an improved one pot process for synthesis of acyl thioureas of formula (I), with yield greater than 80%, from aroyl chlorides of formula (I) wherein, R′ is an aryl or a heteroarylene group substituted with one or more groups selected from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino, carboxyl, ester, halogenated hydrocarbon or an aryl or heteroaryl; R″ and R′″ are selected independently from hydrogen, alkyl, alkylene, alkynyl, alkoxy, alkenyloxy, halo, hydroxyl, nitro, amino or halogenated hydrocarbon.

Synthesis of C-disaccharides through a one-pot alkynol cycloisomerization-reductive deoxygenation - Narute, Sachin B.; Rout, Jeetendra Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2013)
Keywords: C-disaccharides; carbohydrates; Epoxide-alkyne coupling; Gold catalysis; Reductive deoxygenation

Synthesis of pseudo-indoxyl derivatives via sequential Cu-catalyzed SNAr and Smalley cyclization - Goriya, Yogesh; Ramana, Chepuri V. (Chemical Communications, 2013)
ortho-Bromophenyl sec-alkyl/sec-alkenyl ketones, on reaction with sodium azide in the presence of copper salts, undergo sequential SNAr followed by Smalley cyclization to provide pseudo-indoxyl derivatives. Some of these pseudo-indoxyl derivatives exhibit interesting fluorescent properties and broad Stokes shifts.

2-Aroylindoles from o-bromochalcones via Cu(I)-catalyzed SNAr with an azide and intramolecular nitrene C-H insertion - Goriya, Yogesh; Ramana, Chepuri V. (Chemical Communications, 2014)
A simple procedure for the synthesis of 2-aroylindole derivatives comprising a one-pot CuI-catalyzed SNAr reaction of o-bromochalconeswith sodium azide and subsequent intramolecular cyclization through nitrene C-H insertion has been developed. This protocol is also applicablewith the 2'-bromocinnamates giving the indole-2-carboxylates.

Gold(I)-catalysed [1,3] O -> C rearrangement of allenyl ethers - Kona, Chandrababu Naidu; Ramana, Chepuri V. (Chemical Communications, 2014)
A simple and rapid access to the alpha-substituted acryl aldehydes has been provided by developing a gold-catalysed [1,3] rearrangement of the allenyl ethers importantly with a record turnover frequency of 4600 h(-1) (at 0.05 mol% of the catalyst concentration) in homogeneous gold(I) catalysis.

Optimization of the anti-cancer activity of the phosphatidylinositol-3 kinase pathway inhibitor PITENIN-1: switching thiourea with 1,2,3-triazole - Kommagalla, Yadagiri; Cornea, Sinziana; Riehle, Robert; Torchilin, Vladimir; Degterev, Alexei; Ramana, Chepuri V. (Medchemcomm, 2014)
We previously reported encouraging in vitro and in vivo anti-cancer activity of N-((3-chloro-2-hydroxy-5-nitrophenyl)carbamothioyl) benzamide (termed PITENIN-1). In the current work, we describe the structure-activity relationship study of the PIT-1 series, based on the replacement of a central thiourea unit with 1,2,3-triazole, which leads to increased liver microsomal stability, drug likeness and toxicity towards cancer cells.

Ru-catalyzed branched versus linear selective C3-alkylation of 2-aroylbenzofurans with acrylates via C-H activation - Kommagalla, Yadagiri; Srinivas, Kolluru; Ramana, Chepuri V. (Chemistry-A European Journal, 2014)
The carbonyl-directed C3-H activation and alkylation of 2-aroylbenzo[b]furans with acrylates occurs selectively either in a linear or branched fashion, depending on the catalyst employed; [Ru(p-cymene)Cl-2](2) or Ru(PPh3)(3)Cl-2, respectively. Two alternate pathways-funded upon the differences in steric and electronic preferences of these two complexes-is proposed for the selectivity of linear versus branched products.
Keywords: acrylate; benzo[b]furan; branched-selective alkylation; C-H activation; ruthenium

Total synthesis of the putative structure of xylarinol B - More, Atul A.; Ramana, Chepuri V. (Chemistry-An Asian Journal, 2014)
The total synthesis of the putative structure of xylarinolB is described and the need to revise its structure is demonstrated. The central benzoxepine skeleton was constructed by employing a cobalt-mediated bimolecular [2+2+2] Reppe-Vollhardt alkyne cycloaddition reaction.
Keywords: Chiral pool; cobalt; Natural products; structure elucidation; Total synthesis

Tuning the regioselectivity of gold-catalyzed internal nitroalkyne redox: a cycloisomerization and [3+2]-cycloaddition cascade for the construction of spiro-pseudoindoxyl skeleton - Kumar, Chepuri V. Suneel; Ramana, Chepuri V. (Organic Letters, 2014)
A simple domino process for the construction of the tricyclic core present in the spiro-pseudoindoxyl natural products has been developed. This involves two intramolecular events: the Au-catalyzed nitroalkyne redox leading to isatogen and its subsequent [3 + 2]-cycloaddition with a suitably positioned olefin. The option to modulate the size of the spiro-annulated ring, which is an important variable in this class of natural products, has been explored. Overall, this process molds a linear precursor into a tricyclic system with complete step, atom, and redox economy.

Formal total synthesis of (-)-kumausallene - Das, Shyamsundar; Ramana, Chepuri V. (Tetrahedron, 2015)
Deacetylkumausyne-a penultimate intermediate in Tang's total synthesis of (-)-kumausallene has been synthesized employing a chiral pool approach and thus culminating in a formal total synthesis of kumausallene. The opening of an epoxide with alkyne (use of Birch reduction for the selective construction of E-pent-3-enyl group) and C-allylation have been used to introduce the pendant alkenyl side chains. Initial attempts to execute an alternative to Tang's route comprising a prior installation of the bromoallene unit via bromoetherification and subsequent S(N)2 displacement are unsuccessful. To overcome this, an alternative approach was developed to arrive at Deacetylkumausyne (another natural product that has been synthesized and characterized by Tang's group). Thus, this overall exercise has culminated in a formal total synthesis of (-)-kumausallene. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Bis-THF natural products; Chiral pool; Deacetylkumausyne; Total synthesis; Wittig reaction

Gold(I)-catalyzed hydroindolylation of allenyl ethers - Kona, Chandrababu Naidu; Shinde, Mahesh H.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2015)
The gold(I)-catalyzed reaction/rearrangement of allenyl ethers has been investigated in the presence of indoles. Either hydroindolylation or alkylation of an indole with the pendant group of allenyl ether has been observed. The reaction outcome seems to be decided mainly by the nature of the pendant group of the allenyl ether. Control experiments are indicative of an inner sphere mechanism for the hydroindolylation reaction.

Oxone-acetone mediated syn-dioxygenation of benzo-fused olefins - Phatake, Ravindra S.; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The oxone-acetone combination well established for olefin epoxidation has been demonstrated to be a practical reagent for the syn-dioxygenation (resulting in 1,3-dioxolanes) of indenes and dihydronaphthalenes. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dihydronaphthalene; Dioxygenation; Indene; Oxone

Oxone-acetone mediated wacker-type oxidation of benzo-fused olefins - Phatake, Ravindra S.; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
Herein we disclose a novel application of the oxone-acetone combination for the Wacker-type oxidation of indenes and dihydronaphthalenes leading, respectively, to indan-2-ones and 2-tetralones. The amount of the base employed in the reaction seems to switch the reaction path from dioxygenation to Wacker-type oxidation. Control experiments suggest that the reaction is not proceeding via the epoxide route and also that there is no role of trace amounts of metals present in the reagents on the current oxidation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Dihydronaphthalene; Indene; Oxone; Wacker oxidation

Ru-catalyzed redox-neutral cleavage of the N-O bond in isoxazolidines: isatogens to pseudoindoxyls via a one-pot [3+2]-cycloaddition/N-O cleavage - Kumar, Chepuri V. Suneel; Ramana, Chepuri V. (Organic Letters, 2015)
A novel metal-catalyzed oxygen atom transfer reaction onto olefins is reported. By taking isatogens as substrates, a one-pot [3 + 2]-cycloaddition of nitrone with olefins followed by the Ru-catalyzed redox-neutral N-O bond cleavage of intermediate isoxazolidine has been executed as a simple method for the synthesis of 2,2-disubstituted pseudoindoxyls.

Ruthenium(II)-catalyzed C3 arylation of 2-aroylbenzofurans with arylboronic acids/aryltrifluoroborates via carbonyl-directed C-H bond activation - Paymode, Dinesh J.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2015)
The Ru(II)-catalyzed carbonyl-directed C-H activation with (hetero)arylboron reagents has been executed for the synthesis of 2-aroyl-3-(hetero)arylbenzofurans. A hypothesis founded upon the involvement Of an active carbonatoruthenium(II) complex for a coordinative insertion and the aerobic oxidation of the in situ generated Ru(0) to Ru(II), to continue the catalytic cycle, has been extended.

Ruthenium(II)-catalyzed switchable C3-alkylation versus alkenylation with acrylates of 2-pyridylbenzofurans via C-H bond activation - Kommagalla, Yadagiri; Mullapudi, Venkanna Babu; Francis, Fredi; Ramana, Chepuri V. (Catalysis Science & Technology, 2015)
We documented an interesting observation of ruthenium (II)-catalyzed benzofuran C-H activation and subsequent functionalization with acrylates that reveals that a simple base can switch the process from alkylation to alkenylation.

Target cum flexibility: synthesis of indolo[1,2-b]isoquinoline derivatives via cobalt-catalyzed [2+2+2] cyclotrimerization - Swami, Anuradha; Ramana, Chepuri V. (Synlett, 2015)
A modular approach for the synthesis of small molecules having the unnatural 6,11-dihydroindolo[1,2-b]isoquinoline tetracyclic core has been documented. An acid-catalyzed Friedel-Crafts-type C2-alkylation of N-propargyl indole with a suitably activated alkynol has been used to prepare the key indole-derived diynes. The cobalt-catalyzed [2+2+2] cyclotrimerization of these diynes has been studied with various internal/terminal alkynes and with nitriles.
Keywords: 2-b]-isoquinoline; cobalt; Indole; indolo[1; Pyridine; [2+2+2] cyclotrimerization

Total synthesis of (+)-petromyroxol - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Tetrahedron Letters, 2015)
The total synthesis of (+)-petromyroxol establishing its absolute configuration has been accomplished. The strategy developed employs easily accessible carbohydrate building blocks and comprises flexible and scalable chemistry that allowed the synthesis of (+)-petromyroxol along with its three diastereomers varying the stereochemistry mainly at C5 and/or C6. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Glucose diacetonide; Petromyroxol; Pheromone; Sea Lamprey; Total synthesis

Total synthesis of sinenside A - Vadhadiya, Paresh M.; Ramana, Chepuri V. (Organic Letters, 2015)
The first total synthesis of norlignan glucoside sinenside A has been accomplished. An intramolecular acetalization reaction has been employed as the key skeletal construct to forge the central cyclic disaccharide core. The trans-1,2-diol configuration present in the cyclic disaccharide of this natural product is unique and has been addressed by setting this configuration at the beginning. A 1,2-orthoester group has been selected as a handle for both sp glycosidation and for differentiation of the C2'-OH (that participates in the key acetalization reaction) of the sugar unit.

Alkyne [2+2+2]-cyclotrimerization approach for synthesis of 6,7-cyclopropylallocolchicinoids - More, Atul A.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2016)
Employing a cobalt-catalyzed [2 + 2 + 2] alkyne cyclotrimerization as the final step, the short and efficient synthesis of cyclopropylallocolchicinoid and its analogues having functional group variations at C9 and/or C10 and C11 of ring C has been accomplished.

Cu-catalyzed sequential C-N bond formations: expeditious synthesis of tetracyclic indoloindol-3-ones - Kulkarni, Anand M.; Srinivas, Kolluru; Deshpande, Mukund V.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
The tetracyclic indoloindol-3-one core has been forged from easily accessible 2,2'-bis-bromochalcones employing a reaction cascade comprising Cu-catalyzed SNAr with azide; nitrene C-H insertion and intramolecular Ullmann reaction with all three C-N bond formations in one-go.

Fluoride-mediated dephosphonylation of α-diazo-β-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkanna Babu; Wakchaure, Vivek Chandrakant; Ramana, Chepuri V. (Organic Letters, 2016)
The possibility of fluoride-mediated selective dephosphonylation of α-diazo-β-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting α-diazocarbonyl intermediates undergo a (3 + 2)-cycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess α-diazo-β-carbonyl phosphonates) or Michael addition (with conjugated olefins).

Fungal cell membrane-promising drug target for antifungal therapy - Sant, D. G.; Tupe, Santosh Genba; Ramana, Chepuri V.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2016)
Increase in invasive fungal infections over the past few years especially in immunocompromised patients prompted the search for new antifungal agents with improved efficacy. Current antifungal armoury includes very few effective drugs like Amphotericin B; new generation azoles, including voriconazole and posaconazole; echinocandins like caspofungin and micafungin to name a few. Azole class of antifungals which target the fungal cell membrane are the first choice of treatment for many years because of their effectiveness. As the fungal cell membrane is predominantly made up of sterols, glycerophospholipids and sphingolipids, the role of lipids in pathogenesis and target identification for improved therapeutics were largely pursued by researchers during the last few years. Present review focuses on cell membrane as an antifungal target with emphasis on membrane biogenesis, structure and function of cell membrane, cell membrane inhibitors, screening assays, recent advances and future prospects.

Gold(I) catalyzed [1,3] O -> C rearrangement of benzylvinyl ethers - Kona, Chandrababu Naidu; Patil, Mahesh N.; Ramana, Chepuri V. (Organic Chemistry Frontiers, 2016)
A simple procedure for the preparation of 3-(hetero) arylpropionaldehydes has been developed employing a gold-catalyzed [1,3]-rearrangement of vinyl ethers. Using this protocol, Canthoxal, an aromatic aldehyde used in perfumery, has been prepared on a gram scale.

Ir(III)-catalyzed carbenoid functionalization of benzamides: synthesis of N-methoxyisoquinolinediones and N-methoxyisoquinolinones - Phatake, Ravindra S.; Patel, Pitambar; Ramana, Chepuri V. (Organic Letters, 2016)
A mild and efficient Ir(III)-catalyzed C-H carbenoid functionalization strategy has been developed to access. N-methoxyisoquinolinediones and N-methoxyisoquinolinones. The reaction proceeds efficiently in high yield at room temperature over a broad range of substrates without requirement of any additional oxidants or a base.

Ir(III)-catalyzed synthesis of isoquinoline N-oxides from aryloxime and alpha-diazocarbonyl compounds - Phatake, Ravindra S.; Patel, Pitambar; Ramana, Chepuri V. (Organic Letters, 2016)
An efficient Ir(III)-catalyzed C-H activation and annulations of aryloxime with a-diazocarbonyl compounds has been developed for the synthesis of substituted isoquinoline N-oxides. The reaction proceeds under mild atmospheric conditions, without any external oxidants and releases N-2 and H2O as the byproducts. In addition, synthetic applications of the N-oxide products have been established by performing further functionalization. An interesting dimeric iridacyclic complex allied through a bis-silver carboxylate bridge has been isolated that efficiently catalyzed the reaction.

O-Quinone methides via oxone-mediated benzofuran oxidative dearomatization and their intramolecular cycloaddition with carbonyl groups: an expeditious construction of the central tetracyclic core of integrastatins, epicoccolide A, and epicocconigrone A - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The intramolecular cycloaddition of o-quinone methides (o-QMs) with a carbonyl group has been envisaged and executed successfully in the context of constructing the complex and rare [6,6,6,6]-tetracyclic core found in the integrastatins, epicoccolide A, and epicocconigrone A. These transient o-QMs were generated easily from the oxidative dearomatization of the corresponding C2-(aryl)benzofuran by employing Oxone in acetone-water at rt. The subsequent cydoaddition with the carbonyl (or conjugated olefin) present on the C2-aryl group was spontaneous.

Re-engineering of PIP3-antagonist triazole PITENIN's chemical scaffold: development of novel antifungal leads - Pulya, Sravani; Kommagalla, Yadagiri; Sant, Duhita G.; Jorwekar, Shweta U.; Tupe, Santosh G.; Deshpande, Mukund V.; Ramana, Chepuri V. (RSC Advances, 2016)
A novel 4-(1-phenyl-1-hydroxyethyl)-1-(o-hydroxyphenyl)-1H-1,2,3-triazole was designed by integrating the structural features of triazole PITENIN anticancer agents and the azole class of antifungal drugs. A two-step protocol comprising the Barbier propargylation and Cu-catalyzed azide-alkyne cycloaddition was established to synthesise a diverse set of compounds of this class. Their screening against a wide range of human fungal pathogens led to identification of several potential antifungal hits and some of them displayed better antifungal activity than fluconazole against Candida glabrata, Cryptococcus neoformans, Aspergillus fumigatus and Aspergillus niger. Mode of action studies revealed that their antifungal activity was resulting either from the inhibition of lanosterol 14 alpha-demethylase enzyme (leading to ergosterol depletion) or by the generation of reactive oxygen species (ROS).

Synthesis of functionalized 6-hydroxy-2-oxindole derivatives by phenoxide cyclization - Reddy, B. Narendraprasad; Ramana, Chepuri V. (Organic Letters, 2016)
An apparent intramolecular cross-dehydrogenative coupling of N-(3-hydrox)monoanilide of maleic esters comprising base promoted phenoxide cyclization and subsequent base-mediated aerobic oxidation was developed to synthesize a variety of 2-(6-hydroxy-2-oxoindolin-3-ylidene)-acetate derivatives. The isolation of intermediate cyclized products during the large scale reactions and their ready dehydrogenation with 1 equiv of base support this proposed two-step path.

Total synthesis and structural assignment of hexaketide xylarinolb and its C1-epimer - Mullapudi, Venkanna Babu; Ramana, Chepuri V. (Asian Journal of Organic Chemistry, 2016)
The total synthesis of two isomeric hexaketides isolated along with sordarial, which have the proposed relative arabino and ribo configurations, has been executed. A Rh-catalyzed [2+2+2]-alkyne cyclotrimerization has been employed as the key reaction to construct the central dihydroisobenzofuran core. The absolute configuration of the xylarinolB hexaketide has been established as l-arabino. This is the first natural product of this family for which the absolute configuration has been determined, and this can be extended to provide structural details of several of related hexaketides.
Keywords: hexaketides; sordarial; Wilkinson's catalyst; xylarinolB; {[2+2+2]-cyclotrimerization

Total synthesis of integrastatin B enabled by a benzofuran oxidative dearomatization cascade - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The first total synthesis of integrastatin B, a potent HIV-1 integrase inhibitor, has been accomplished in seven steps with a 17.9% overall yield employing easily accessible starting compounds. The Oxone-mediated oxidative benzofuran dearomatization cascade has been employed as the key skeletal construct to forge the central tetracyclic nucleus.

Concise approach for central core of trigolutes: total synthesis of trigolute B and 3-epi-trigolute B and analogues - Reddy, B. Narendraprasad; Ramana, Chepuri V. (Tetrahedron, 2017)
A concise approach comprising a combination of the Pd- or Ir-catalyzed Tsuji-Trost allylation and olefin dihydrox-ylation/acid catalyzed lactonization has been developed to construct the central spirolactone core of trigolutes with the requisite functional groups. A large number of analogues of trigolute B have been synthesized. Furthermore, the synthesis of both (±)-trigolute B and (±)-3-epi-trigolute B has been accomplished in 4–5 steps from easily accessible building blocks.

Electronic control on linear versus branched alkylation of 2-/3-aroylbenzofurans with acrylates: combined DFT and synthetic studies - Srinivas, Kolluru; Dangat, Yuvraj; Kommagalla, Yadagiri; Vanka, Kumar; Ramana, Chepuri V. (Chemistry-A European Journal, 2017)
Investigations on the factors that govern unusual branched alkylation of 2-aroylbenzofurans with acrylates by Ru-catalyzed carbonyl-directed C-H activation has been carried out by calculating the kinetics associated with the two key steps-the coordination of the acrylate with the intermediate ruthenacycle and the subsequent migratory insertion reaction-studied with the help of DFT calculations. Eight possible orientations for each mode of alkylation have been considered for the calculations. From these calculations, it has been understood that there is a synergistic operation of the steric and electronic effects favoring the branched alkylation. Further DFT investigations on the alkylation of the isomeric 3-aroylbenzofurans indicated a preference for the linear alkylation and this has been verified experimentally. Overall, the observed/calculated complementary selectivity in the alkylation of 2-/3-aroylbenzofurans with acrylates reveals that the substrate-dependent charge distribution of the Ru-C bond in the intermediate ruthenacycle is an important determining factor and thus the current work opens up a new domain of substrate design for controlling regioselectivity.
Keywords: acrylates; Alkylation; aroylbenzofuran; C-H activation; Density functional calculations

Fluoride-mediated dephosphonylation of alpha-diazo-beta-carbonyl phosphonates - Phatake, Ravindra S.; Mullapudi, Venkannababu; Wakchaure, Vivek C.; Ramana, Chepuri V. (Organic Letters, 2017)
The possibility of fluoride-mediated selective dephosphonylation of alpha-diazo-beta-carbonyl phosphonates such as the Ohira-Bestmann reagent has been proposed and executed. The resulting alpha-diazocarbonyl intermediates undergo a (3 + 2)pcycloaddition at room temperature with conjugated olefins and benzynes. Interestingly, under the current conditions, the resulting cycloaddition products underwent either N-acylation (with excess alpha-diazo-beta-carbonyl phosphonates) or Michael addition (with conjugated olefins).

Interrupting base-mediated benzofuran ring transformation with michael acceptors - Srinivas, Kolluru; Sharma, Rashmi; Ramana, Chepuri V. (Journal of Organic Chemistry, 2017)
A simple two-stage approach for the synthesis of 3-(2-arylbenzofuran-3-yl)propanoates and propanamides has been developed employing simple acrylates and acrylamides and readily available 3-aroylbenzofurans. The key step of this process involves a base-mediated ring opening of the 3-aroylbenzofurans and subsequent Michael addition of the resulting 1,3-dicarbonyl intermediate with acrylate/acrylamide, followed by the deformylation in one-pot. The resulting products undergo an acid-mediated dehydrative cyclization to arrive at these targets.
Keywords: Acyl Benzylic Bromides; Beta-Ketoaldehydes; Efficient Synthesis; Ortho-Hydroxybenzyl Ketones; Phenols; Position; Precursors; Sur Le Benzofuranne; Transposition

Phenol oxidative dearomatization of modified nucleoside templates: a simple access to the c7-spiroannulated octosyl acid framework - Mullapudi, Venkannababu; Bhogade, Ravindra B.; Deshpande, Mukund V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2017)
Phenol oxidative dearomatization and cyclization has been executed successfully on nucleoside templates to synthesize C7-spiroannulated perhydrofuropyran nucleosides and C6-spiroannulated perhydrofurofuran nucleosides as novel analogues of octosyl acid and related peptidyl nucleosides.
Keywords: Analogs; antibiotics; Biosynthesis; Chitin synthase; Derivatives; Ezomycins; Glucose Diacetonide Natural-products; Griseofulvin; Malayamycin; Modified nucleosides; Moiety; Peptidyl Glycosides; Phenol Oxidative Dearomatization; Vorbruggen Glycosylation

Total synthesis of (+/-)-allocolchicine and its analogues using Co-catalyzed alkyne [2 - Paymode, Dinesh J.; Ramana, Chepuri V. (ACS Omega, 2017)
The total synthesis of (+/-)-allocolchicine has been completed by employing cobalt-catalyzed alkyne [2 + 2 + 2]-cyclotrimerization as the key reaction. The essential diyne has been synthesized from easily available 3,4,5-trimethoxybenzaldehyde following simple chemical transformations. In general, the cycloaddition gave a mixture of C(9) and C(10) isomers thus allowing the synthesis of both allocolchicine and its C(10)-carboxylate. Because this cycloaddition was employed at the penultimate stage, it allowed the synthesis of various analogues having the diverse functionality at C(9) and/or C(10) of ring C.

Total synthesis of propolisbenzofuran B - Srinivas, Kolluru; Ramana, Chepuri V. (Organic Letters, 2017)
An efficient synthesis of propolisbenzofuran B, which possesses promising anticancer activity, is reported. The key cyclohexanone framework of this tricyclic natural product has been constructed employing a Rh-catalyzed intramolecular olefin hydroacylation. The requisite key olefin intermediate was synthesized by using gold-catalyzed allenyl ether [1,3] O -> C rearrangement.

Total synthesis of notoryne - Senapati, Sibadatta; Das, Shyamsundar; Ramana, Chepuri V. (Journal of Organic Chemistry, 2018)
The structure of notoryne comprises a halogenated 2,2'-bifuranyl moiety along with a terminal cis-enyne unit. In this work, we document the first total synthesis of notoryne, confirming its assigned relative and absolute configurations. The devised route comprises a glucose diacetonide-derived chiral pool intermediate as the starting point and 5-endo bromo-etherification for making the key bis-furan unit, anomeric C-allylation, as well as a relay cross-metathesis to install the cis-enyne unit.

Iridium(III)-catalyzed alkynylation of 2-(Hetero)arylquinazolin-4-one scaffolds via C-H bond activation - Rohokale, Rajendra S.; Kalshetti, Rupali G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
The directed C-H alkynylation of 2-(hetero)arylquinazolin-4-ones has been explored with the ethynylbenziodoxolone reagent TIPS-EBX employing an Ir(III) catalyst. Complementary conditions for either monoalkynylation or dialkynylation have been developed. Also demonstrated is the broad scope of this reaction and the compatibility of various functional groups such as -F, -Cl, -Br, -CF3, -OMe, -NO2, and alkyl, etc.

Ru(II)-catalyzed C-H activation/alkylation of 3-formylbenzofurans with conjugated olefins: product divergence - Srinivas, Kolluru; Siddiqui, Shaziyaparveen K.; Mudaliar, Jyothi K.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2019)
Ru-catalyzed alkylation of 3-formylbenzofuran with acrylates and acrylamides has been described. Branched selectivity with unsubstituted or beta-substituted acrylates/ acrylamides and linear selectivity with alpha-substituted acrylates have been observed. However, in all of the cases, the intermediate alkylation products seem to undergo further reactions, either cycloannulation or deformylation, depending on the substrate employed. For example, with methyl acrylate, the intermediate branched alkylation product underwent cycloannulation with another molecule of methyl acrylate, resulting in a densely functionalized cyclohexene ring formation. On the other hand, in the case of N-monosubstituted acrylamides, the branched alkylation proceeded with intramolecular aldehyde-amide condensation, leading to pyridin-2-one ring annulation. However, with both methacrylate and crotonate, deformylation of the initially formed alkylation products was observed.

Apparent umpolung reactivity of indole through [Au]-catalysed cyclisation and lewis-acid-mediated allylation - Shinde, Mahesh H.; Ramana, Chepuri V. (Chemistry-A European Journal, 2020)
The sequential functionalization of indole C2 and C3 in an umpolung fashion was executed with a predesigned substrate and choice of reagents. The developed method comprises gold-catalysed alkynol cycloisomerisation/intramolecular addition of C2 of indole and subsequent BF3.OEt2-mediated regioselective C3 allylation, resulting in the synthesis of the functionalized indoloisoquinolinone scaffold. The reaction involves 5-endo-alkynol cycloisomerisation and the dearomative addition of indole C2 to the intermediate oxocarbenium cation, which results in two equilibrating fused and spiropentacyclic intermediates, which upon treatment with allyl silane in the presence of BF3.OEt2, undergo selective indole C3 allylation. Other nucleophiles, such as hydride, azide and indole, were also found to be compatible with this process.
Keywords: Allylation; cyclization; domino reactions; Gold; umpolung

Total synthesis of (+)-petromyroxol (vol 56, pg 3933, 2015) - Mullapudi, Venkannababu; Ramana, Chepuri V. (Tetrahedron Letters, 2020)

Gold-catalysed nitroalkyne cycloisomerization - synthetic utility - Dhote, Pawan S.; Halnor, Swapnil V.; Ramana, Chepuri V. (Chemical Record, 2021)
The gold-catalysed intramolecular redox cyclization of o-alkynylnitrobenzens documented by Professors Naoki Asao and Yoshinori Yamamoto is an important discovery that has opened two complementary research domains. Advancing this cyclization with other metals as well as developing new methods around the products that result from this reaction is one aspect that has seen growing interest. On the other hand, the idea of generating alpha-oxo gold carbenes via oxygen transfer to alkynes has established another important aspect in gold-catalysis. In this account, we will be dealing with the first aspect, which revolves around the internal redox cyclization of nitroalkynes (trivially called as nitroalkyne cycloisomerization), focusing mainly on the gold-complexes and the synthetic methods developed around it from our group and from other groups, and also providing the details of similar transformations documented with other metals so that the complementary reactivity/diversity of these transformations could be appreciated.
Keywords: alpha-Oxo Gold Carbene; Anthranil; Gold-catalysis; Internal Redox Cyclization; Isatogen

Total synthesis of the pseudoindoxyl class of natural products - Dhote, Pawan S.; Patel, Pitambar; Vanka, Kumar; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2021)
The pseudoindoxyl sub-structural motif, amongst the large set of the indole class of alkaloids, represents a unique subset of the oxygenated indole class of the alkaloid family. A majority of this class of natural products contains complex bridged/polycyclic scaffolds with interesting biological profiles. They are thus attractive synthetic targets. Starting from 1963, twenty-eight natural products having the pseudoindoxyl scaffold have been isolated, among which the synthesis of 13 natural products has been accomplished. In this review, we highlight the completed as well as the formal total synthesis of the natural products with a spiro-pseudoindoxyl ring, with a focus on their development. The challenges and the future perspective based on the recent developments in the field will also be discussed. We strongly believe that this review will not only update but also attract the attention of researchers in dealing with the synthesis of pseudoindoxyl compounds.

Unified approach for the total aynthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification

Unified approach for the total synthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification

Concise approach for the synthesis of the tetracyclic framework of Lycibarbarines A and B - Shet, Manoj N.; Nechooli, Hemanth K.; Ramana, Chepuri V. (Tetrahedron Letters, 2023)
A simple approach for the construction of the tetracyclic spiroketal skeleton of Lycibarbarine A and B has been described. Employing a solvent free condition for epoxide opening with tetrahydroquinoline as a key reaction to couple both the fragments, an oxidation followed by TBAF-mediated silyl deprotection spiroketalization establishes the complete tetracyclic core present in these natural products. (c) 2023 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool approach; D -Glyceraldehyde; Tetracyclic spiroketal; Total synthesis

Rh-catalyzed C-H functionalization of the (Pyrazol-5-yl)pyridine core of GBT-440 - Kalshetti, Rupali G.; Halnor, Swapnil V.; Ramana, Chepuri V. (Synthesis-Stuttgart, 2023)
The Rh-catalyzed cross dehydrogenative coupling (CDC)/alkylation of the pyrazolylpyridine unit of GBT-440 proceeded smoothly under ambient conditions and selectively on the pyrazole unit while directed by the pyridine. The scope of these reactions was established by employing simple as well as conjugated olefins for CDC and various diazo esters and the TIPS-EBX reagent for alkylation. At the outset, a focused small molecule library around the bis-heterocyclic core of GBT440 was developed via C-H functionalization.
Keywords: C-H activation; cross dehydrogenative coupling; diazo ester; GBT-440; Rh catalysis; TIPS-EBX

Attempted synthesis of the central 2,2-disubstituted pseudoindoxyl core of Austamide via a [Au]-catalyzed nitroalkyne cycloisomerization and intramolecular [3+2]-cycloaddition - Halnor, Swapnil V.; Ramana, Chepuri V. (Tetrahedron, 2024)
Herein, we describe an Au-catalyzed cycloisomerization process of a nitroalkyne that was projected to construct the central 2,2-disubstituted pseudoindoxyl core of the natural product Austamide. Our intended strategy for forging the pseudoindoxyl core is based on the nitroalkyne cycloisomerization followed by a subsequent intramolecular [3 + 2] cycloaddition. However, the [3 + 2] cycloaddition occurred in an undesired manner, ultimately leading to a complex hexacyclic scaffold.
Keywords: Austamide; Gold catalysis; Intramolecular [3+2] cycloaddition; Nitroalkyne cycloisomerization

Intramolecular nitrone interrupted click reaction - Pothi, Tejas A.; Ramana, Chepuri V. (Organic Letters, 2024)
We document the intramolecular interception of a Cu-catalyzed azidoalkyne cycloaddition employing a suitably placed nitrone group, providing a simple route to the unprecedented spiro-polyheterocyclic scaffold. The reaction is comprised of a Cu-catalyzed [3 + 2]-cycloaddition of (2-azidoaryl)isatogen with a terminal alkyne and the intramolecular trapping of the transient Cu-triazolide intermediate with the isatogen, with a net formation of one C-C and two C-N bonds and the new heterocyclic ring being spiro-annulated.

Synthesis, characterization, and crystal structure of 2-(2-azidophenyl)-3-oxo-3H-indole 1-oxide - Dhote, Pawan; Tothadi, Srinu; Ramana, Chepuri V.; Chopra, D. (Acta Crystallographica Section E Crystallographic Communications, 2024)
<div class="abstract author" id="aep-abstract-id5" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> An attempt to explore the reactivity of the nitro group in the presence of gold catalysis in comparison to the azide group yielded intriguing results. Surprisingly, only the nitro group exhibited reactivity, ultimately giving rise to the formation of the title isatogen. <div class="abstract author" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> An attempt to explore the reactivity of the nitro group in the presence of gold catalysis in comparison to the azide group yielded intriguing results. Surprisingly, only the nitro group exhibited reactivity, ultimately giving rise to the formation of the title isatogen, C14H8N4O2. In the crystal structure, weak C—H⋯O hydrogen bonds and π–π stacking interactions link the molecules. The structure exhibits disorder of the molecule.

Synthesis of tetracyclic benzoxazolo-indol-3-ones from isatogens and arynes through a [3+2]-cycloaddition and skeletal reorganization - Halnor, Swapnil V.; Singh, Maneesha; Dhote, Pawan S.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2024)
The construction of an unprecedented tetracyclic benzoxazolo-indol-3-one scaffold has been executed through the [3 + 2]-cycloaddition of isatogens with arynes. The initially formed benzisoxazolo-indol-3-one intermediate undergoes a skeletal reorganization through a 1,3-sigmatropic shift/retro-Mannich reaction with the net formation of one C-N and two C-O bonds. The Lewis acid-catalyzed allylation of some of the resulting benzoxazolo-indol-3-ones resulted in oxazepino-indolones with promising photophysical properties.

Total synthesis of (-) and (+)-zingibergingerols A - Shet, Manoj N.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2024)
The first total synthesis of both of the enantiomers of Zingibergingerol A has been accomplished. The distinctive 3,7,9-trioxabicyclo[4.2.1]nonane skeleton is crafted through gold-catalyzed alkynol cycloisomerization. The synthesis comprises sequential C-C bond formations at both ends of epichlorohydrin: first opening the epoxide with eugenol-derived alkyne, followed by subsequent epoxide installation, and again opening with a Grignard reagent. The resulting alkynol with a fixed C5 stereochemistry was subjected to O-allylation, followed by dihydroxylation and alkynol cycloisomerization.

Total synthesis of (±)-streptoglyceride A and of putative (±)-streptoglyceride C - Khobragade, Virendra R.; Ramana, Chepuri V. (Organic Letters, 2025)
The first total synthesis of (+/-)-Streptoglyceride A-one of the early members of this family to be isolated-has been accomplished, along with the synthesis of the putative structure of (+/-)-Streptoglyceride C. The unique tricyclic ring present in these natural products has been constructed by employing a gold-catalyzed tandem diynol cycloisomerization followed by one-pot dihydroxylation/trans-glycosylation. The pendant diene unit was fabricated by Takai olefination and subsequent Stille coupling.

Total synthesis of lucidimines/ganocalicines A/B, sinensine E, and ganocochlearine E - Sai, Godi Kiran Venkata; Ramana, Chepuri V. (Organic Letters, 2026)
The central tetracyclic framework shared by the Ganoderma alkaloids-lucidimines/ganocaclicines A and B, sinensine E, and ganocochlearine E-appears inherently predisposed to arise from a diyne-nitrile cyclotrimerization event. A Co(I)-catalyzed intramolecular [2 + 2 + 2]-alkynenitrile cyclotrimerization has been employed to accomplish the first racemic and enantioselective total syntheses of sinensine E, lucidimine A, and ganocochlearine E, thereby establishing/revising their assigned stereochemical structures.

Total synthesis of triplinone F - Shet, Manoj N.; Wabale, Krishna R.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2026)
The first total synthesis of triplinone F, along with its C11 epimer, has been executed to establish, inter alia, the stereochemistry of C11 and its complete absolute configuration. The terminal styrene unit was added by cross-metathesis, whereby 1,3-diol units on either side of the central olefin were taken from malic acid enantiomers and coupled by a Yamaguchi alkyne-epoxide opening protocol. The C11 stereochemistry was manipulated by Noyori asymmetric ynone reduction. The Z-selective reduction of alkynoate and acid-catalyzed lactonization forged the right-hand-side 5,6-dihydro-delta-pyrone unit.